Intraoperative real-time navigation and intraoperative three-dimensional imaging for patient-specific total temporomandibular joint replacement. Issue 10 (October 2021) - Neuhaus, M.-T.; Zeller, A.-N.; Jehn, P.; Lethaus, B.; Gellrich, N.-C.; Zimmerer, R.M.
Abstract: Customized solutions for replacement of the temporomandibular joint (TMJ) along with surgical guides enable precise and fast transfer of the virtual plan to the patient. However, these guides lack information on screw vectors and length, and well-defined borders for bony resections towards the medial skull base. This retrospective study was performed to investigate the feasibility and benefit of real-time navigation and intraoperative three-dimensional imaging during total TMJ replacement (TJR), as well as patient clinical outcomes. Between 2016 and 2020, 26 customized prostheses were implanted in 21 patients either with or without real-time navigation and instrument tracking. The clinical, surgical, radiological, and navigational data were analysed. The accuracy of navigation registration with instrument tracking, precision of screw insertion, and implant and screw positions were analysed by fusion of the virtual plan and surgical outcome. Real-time navigation aided orientation during lateral skull base dissection and resection. However, the results of real-time navigation-aided drilling were inconclusive regarding vector and length control. At a mean 15.3 ± 3.0 months of follow-up, average mouth opening had improved from 21.69 ± 2.80 mm to 36.40 ± 1.25 mm; the average pain score decreased from 6.18 ± 0.74 to 1.06 ± 0.52. Thus, intraoperative real-time navigation for TJR assists lateral skull base dissection and resection.